Highly efficient and bending durable perovskite solar cells: toward a wearable power source. Issue 3 (27th October 2014) - Kim, Byeong Jo; Kim, Dong Hoe; Lee, Yoo-Yong; Shin, Hee-Won; Han, Gill Sang; Hong, Jung Sug; Mahmood, Khalid; Ahn, Tae Kyu; Joo, Young-Chang; Hong, Kug Sun; Park, Nam-Gyu; Lee, Sangwook; et al.
Abstract : We report annealing-free compact TiO x layer by atomic layer deposition for high efficiency flexible perovskite solar cells, and maintained 95% of the initial PCE after 1000 bending cycles with 10 mm bending radius. Abstract : Perovskite solar cells are promising candidates for realizing an efficient, flexible, and lightweight energy supply system for wearable electronic devices. For flexible perovskite solar cells, achieving high power conversion efficiency (PCE) while using a low-temperature technology for the fabrication of a compact charge collection layer is a critical issue. Herein, we report on a flexible perovskite solar cell exhibiting 12.2% PCE as a result of the employment of an annealing-free, 20 nm thick, amorphous, compact TiO x layer deposited by atomic layer deposition. The excellent performance of the cell was attributed to fast electron transport, verified by time-resolved photoluminescence and impedance studies. The PCE remained the same down to 0.4 sun illumination, as well as to a 45° tilt to incident light. Mechanical bending of the devices worsened device performance by only 7% when a bending radius of 1 mm was used. The devices maintained 95% of the initial PCE after 1000 bending cycles for a bending radius of 10 mm. Degradation of the device performance by the bending was the result of crack formation from the transparent conducting oxide layer, demonstrating the potential of the low-temperature-processed TiO x layer to achieve more efficient and bendable perovskite solar cells, which becomes closer to a practical wearable power source.